Overexpressed S100A7 in the progression of oral lichen planus: From moderate dysplasia to oral squamous cell carcinoma - Gandolfo, Mariana Silvia (2023)
The S100A7 protein plays an essential role in tumor progression and is found to be overexpressed or deregulated in oral mucosal dysplasia and several cancers. However, its expression in oral lichen planus remains unknown. Early detection of malignancy in lichen is a challenge because the histopathological diagnosis of dysplasia is subjective and is dependent on the personal assessment of each observer and there are intra and interobserver variability. In this context, using biological markers such as S100A7 could estimate its capacity for malignant transformation. The objective is to describe the immunohistochemical expression of S100A7 in a case of malignant transformation of oral lichen planus in a 62-year-old woman, in whom several foci of mild and moderate dysplasia and micro-invasive carcinoma were detected and monitored during her clinical follow-up. Immunohistochemistry of S100A7 determined increased protein expression in moderate dysplasia and micro-invasive carcinoma of oral lichen planus.